Marketing Letters A Journal of Research in Marketing - Bucklin, Randolph E.; Urbany, Joel E.; Kardes, Frank; Steckel, Joel.; Golder, Peter N.; Jap, Sandy; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Marketing Letters: A Journal of Research in Marketing publishes high-quality, shorter paper (under 5,000 words including abstract, main text and references, which is equivalent to 20 total pages, double-spaced with 12 point Times New Roman font) on marketing, the emphasis being on immediacy and current interest. The journal offers a medium for the truly rapid publication of research results. The focus of Marketing Letters is on empirical findings, methodological papers, and theoretical and conceptual insights across areas of research in marketing. Marketing Letters is required reading for anyone working in marketing science, consumer research, methodology, and marketing strategy and management. The key subject areas and topics covered in Marketing Letters are: choice models, consumer behavior, consumer research, management science, market research, sales and advertising, marketing management, marketing research, marketing science, psychology, and statistics. Officially cited as: Mark Lett.
Keywords: Marketing; Marketing